Evaluation of Beauveria bassiana, Metarhizium anisopliae, and Bacillus thuringiensis for the management of Helicoverpa armigera (Hubner) (Lepidoptera: Noctuidae) under laboratory and field conditions. Issue 3 (3rd March 2020) - Fite, Tarekegn; Tefera, Tadele; Negeri, Mulugeta; Damte, Tebekew; Sori, Waktole
ABSTRACT: The old-world bollworm, Helicoverpa armigera (Hubner) (Lepidoptera: Noctuidae), is a destructive pest of chickpeas that has proven difficult to control using conventional methods. We evaluated the virulence of 14 isolates of Beauveria bassiana and Metarhizium anisopliae s.l. and a commercial wettable product of Bacillus thuringiensis ( Bt ) against larvae of H. armigera . Three isolates of B. bassiana, APPRC-9604, APPRC-T5 and DLCO-EA-56, and one of M. anisopliae strain ( DLCO-EA-40 ) were most effective against third instar H. armigera at 10 8 conidia/mL. At this rate, B. bassiana was more virulent to the third instar H. armigera than M. anisopliae. Among the B. bassiana isolates, APPRC-9604 had the highest virulence; i.e. LT50 (4.6 days) and LC50 (1.3 × 10 4 conidia/mL). Field trials indicated that APPRC-9604 is effective in reducing larval infestations, decreasing pod damage and increasing chickpea yield. Wettable powder concentrations of Bt caused higher mortality to second instar (69%) than to third instar (56.5%) H. armigera larvae at 0.2 g/200 mL at 8 days post-treatment. Surviving larvae feeding on Bt -treated chickpea leaves required additional days for pupation and adult emergence and had a shortened adult life span compared to untreated controls. We conclude that APPRC-9604 isolate and Bt show potential as biological control agents of H. armigera larvae. Further research should focus on the effectiveness of Bt products under field conditions.